Introducció al més enllà en l'opus lul'lià. - HOYOS, XAVIER BONILLO (Scripta)
This paper analyzes the conception of some questions of the afterlife in the work of Ramon Llull, from some of the themes of thirteenth century eschatology, as the certainty of paradise and its description, the characteristics of angels or the salvation of the soul.